An enhanced low-frequency vibration ZnO nanorod-based tuning fork piezoelectric nanogenerator. Issue 2 (20th December 2017) - Deng, Weili; Jin, Long; Chen, Yueqi; Chu, Wenjun; Zhang, Binbin; Sun, Huan; Xiong, Da; Lv, Zekai; Zhu, Minhao; Yang, Weiqing
Abstract : An enhanced piezoelectric nanogenerator from low-frequency vibration utilizing a ZnO nanorod-based tuning fork. Abstract : In this paper, a piezoelectric nanogenerator (PENG) based on a tuning fork-shaped cantilever was designed and fabricated, aiming at harvesting low frequency vibration energy in the environment. In the PENG, a tuning fork-shaped elastic beam combined with ZnO nanorods (NRs), instead of conventional rectangular cantilever beams, was adopted to extract vibration energy. Benefiting from the high flexibility and the controllable shape of the substrate, this PENG was extremely sensitive to vibration and can harvest weak vibration energy at a low frequency. Moreover, a series of simulation models were established to compare the performance of the PENG with that of different shapes. On this basis, the experimental results further verify that this designed energy harvester could operate at a low frequency which was about 13 Hz. The peak output voltage and current could respectively reach about 160 mV and 11 nA, and a maximum instantaneous peak power of 0.92 μW cm −3 across a matched load of 9 MΩ was obtained. Evidently, this newly designed PENG could harvest vibration energy at a lower frequency, which will contribute to broaden the application range of the PENG in energy harvesting and self-powered systems.